Fostering Individual and Organizational Creativity in Design - Katharine E. Leigh; Amy M. Huber; Kenneth R. Tremblay, Jr. (Journal of Systemics, Cybernetics and Informatics, 2013)

(untitled)
Demand for creativity has moved from individual to organizational levels encompassing work environments in which organizations, competing for customers and clients, must demonstrate increased creativity and innovation as the pace of change escalates. Creativity, as a means to produce innovative outcomes, invites individuals and organizations to generate and embrace new ideas and ways of accomplishing work tasks. Facilitators of individual and organizational creativity, in non-design organizations, have revealed climate factors consistent in measuring workplace creativity; however, research findings have suggested differences between creative and non-creative environments regarding the importance of resources, time pressure, and autonomy relative to work tasks in studies of architectural and advertising work environments. This paper focuses on findings of two empirical studies used to identify key factors influencing creativity at the individual and organizational levels.